PEREMPUAN DAN MEDIA IKLAN SUATU ANALISIS KETIDAKADILAN DALAM MEDIA SOSIAL - Ihsan, Muhammad Alim (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
In the people'srealities, women's problems and advertising is one thing that cannot be separated, because women in the eye ofsociety become an important scourge in advertisements withoutwomen's identity feels empty and will not create balance in life. Thebalance is that advertising is more likely to build a reality byexploiting norms or values and secondly no single theory isspecifically used to examine gender issues. The theory developed forgender is adopted from the theories that move in the field related togender issues. The theory in question is structural functional theory,conflict theory, feminism theory and others.